V-ATPase activity in the TGN/EE is required for exocytosis and recycling in Arabidopsis - Luo, Yu; Scholl, Stefan; Doering, Anett; Zhang, Yi; Irani, Niloufer G.; Di Rubbo, Simone; Neumetzler, Lutz; Krishnamoorthy, Praveen; Van Houtte, Isabelle; Mylle, Evelien; Bischoff, Volker; Vernhettes, Samantha; et al. (Nature plants, 2015)
In plants, vacuolar H+-ATPase (V-ATPase) activity acidifies both the trans-Golgi network/early endosome (TGN/EE) and the vacuole. This dual V-ATPase function has impeded our understanding of how the pH homeostasis within the plant TGN/EE controls exo- and endocytosis. Here, we show that the weak V-ATPase mutant deetiolated3 (det3) displayed a pH increase in the TGN/EE, but not in the vacuole, strongly impairing secretion and recycling of the brassinosteroid receptor and the cellulose synthase complexes to the plasma membrane, in contrast to mutants lacking tonoplast-localized V-ATPase activity only. The brassinosteroid insensitivity and the cellulose deficiency defects in det3 were tightly correlated with reduced Golgi and TGN/EE motility. Thus, our results provide strong evidence that acidification of the TGN/EE, but not of the vacuole, is indispensable for functional secretion and recycling in plants.